Sonhos Sujos: erratic conversation (Palíndromo, 2020)
Sonhos Sujos is part of Leticia Cardoso’s doctoral research in Contemporary Artistic Processes, directed by Professor Dr. Marta Martins since 2017, when the visual artist while living at Sobrado na Ladeira during the Artistic Residency Award at Elisabete Anderle in 2017 finds that the space during the nineteenth and twentieth century was a sanatorium with experimental treatments for hysteria disorder. During the excavation was found a chest with letters, audios, videos and a wall strikethrough with words and covered by color. The erratic conversation was held between Fábio Noronha and Letícia Cardoso, on September 1st, 2018, in the basement of Sobrado in Ladeira, where the residence was held in Lagoa da Conceição, Santa Catarina Island.
Keywords: hysteria; painting; female; fiction; site-specific